Géographies du savoir historique. Paul-Henri Mallet entre rêves gothiques, germaniques et celtiques - Mohnike, Thomas (Presses universitaires de Rennes, 2019)
The works of Paul-Henri Mallet are considered to be a turning point in the European history of Images of the North. This article aims to show that this is partly due to his specific style of conceptualising an imaginative geography of origins that may in turn be explained as a result of Mallet’s specific place and travels in a geography of European knowledge production. The North is imagined to be the cradle of a European religion and form of government, original to all European people. Differences are explained by the influence of the climate that occurred when groups of people emigrated from the cold North to the warm South, and by the arrival of Christianity. This open imaginative geography, which offered a place for identification to intellectuals in most parts of Europe, was the product of combinations of different local knowledge and traditions of science. The Geneva uprising and education in a Protestant yet Paris-oriented intellectual milieu offered contact with Montesquieu’s desire for a theory of people based on climatic influences, which in turn was partly inspired by Tacitus and Jordanes and therefore by the humanistic Upper Rhine culture. These coordinates of cultural geography where combined with research results of the Scandinavian historical school of Gothicism.